Left cardiac chambers after implantation of mitral valve prostheses “MIX”, “MEDINGE-2”, “KemCor”, and “PeriCor” - N. V. Rogulina (Российский кардиологический журнал, 2013)
Aim. To compare ultrasound parameters of left cardiac chambers after the implantation of mitral valve prostheses “MIX”, “MEDINGE-2”, “KemCor”, and “PeriCor”, using the 10-year follow-up data. Material and methods. We analysed 2,543 echocardiography protocols of patients with mitral valve disease, who in 1995–2008 underwent the implantation of mitral valve prostheses “MIX” (n=122), “MEDINGE-2” (n=67), and biological prostheses “KemCor” or “PeriCor” (n=306). The exclusion criteria were aortal valve prosthesis, prosthesis dysfunction, and age under 18 years. Results and conclusion. In the early post-intervention period, left ventricular (LV) ejection fraction tended to decrease (p>0,10); however, by the end of the first year, it was normalised. The use of biological prostheses resulted in a significant (p